Metronomic Four-Drug Regimen Has Anti-tumor Activity in Pediatric Low-Grade Glioma; The Results of a Phase II Clinical Trial - Verschuur, Arnauld; Heng-Maillard, Marie-Amélie; Dory-Lautrec, Philippe; Truillet, Romain; Jouve, Elisabeth; Chastagner, Pascal; Leblond, Pierre; Aerts, Isabelle; Honoré, Stéphane; Entz-Werle, Natasha; Sirvent, Nicolas; Gentet, Jean-Claude; et al. (Frontiers in Pharmacology, 2018)
Background: Metronomic chemotherapy (MC) is defined as the frequent administration of chemotherapy at doses below the maximal tolerated dose and with no prolonged drug-free break. MC has shown its efficacy in adult tumor types such as breast and ovarian cancer and has to some extent been studied in pediatrics. Objective: To assess the anti-tumor activity and toxicity of a four-drug metronomic regimen in relapsing/refractory pediatric brain tumors (BT) with progression-free survival (PFS) after two cycles as primary endpoint. Methods: Patients ≥4 to 25 years of age were included with progressing BT. Treatment consisted of an 8-week cycle of celecoxib, vinblastine, and cyclophosphamide alternating with methotrexate. Kepner and Chang two-steps model was used with 10 patients in the first stage. If stabilization was observed in ≥2 patients, 8 additional patients were recruited. Assessment was according WHO criteria with central radiology review. Results: Twenty-nine patients (27 evaluable) were included in two groups: ependymoma (group 1, N = 8), and miscellaneous BT (group 2): 3 medulloblastoma (MB), 5 high grade glioma (HGG), 11 low grade glioma (LGG), 2 other BT. After first stage, recruitment for ependymoma was closed [one patient had stable disease (SD) for 4 months]. Cohort 2 was opened for second stage since 1 HGG and 3 LGG patients had SD after two cycles. Recruitment was limited to LGG for the second stage and 2 partial responses (PR), 6 SD and 2 progressive disease (PD) were observed after two cycles. Of these patients with LGG, median age was 10 years, nine patients received vinblastine previously. Median number of cycles was 6.8 (range: 1–12). Treatment was interrupted in five patients for grade 3/4 toxicity. Conclusion: This regimen is active in patients with LGG, even if patients had previously received vinblastine. Toxicity is acceptable. Trial Registration: This study was registered under clinicaltrials.gov – NCT01285817; EUDRACT nr: 2010-021792-81.